2020
DOI: 10.31025/2611-4135/2020.13906
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Throughput Rate and Input Composition on Sensor-Based Sorting Efficiency

Abstract: According to the Directive (EU) 2018/851 of the European Union, higher recycling rates for municipal waste will have to be met in the near future. Beside improvements to the collection systems, the efficiency of mechanical processing and sorting will have to be increased to reach the EU´s targets. Sensor-based sorting (SBS) plants constitute an integral part of today's sorting processes. Two main factors determine the sorting performance: throughput rate and input composition. To improve recycling efficiencies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…However, trials with coarser, rectangular particles created an exponential decrease in yield ( Küppers et al, 2020 ). The form of the respective yield function might be dependent on the particle size distribution of the input material ( Figure 3 ) in dependence of the sorting algorithm.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, trials with coarser, rectangular particles created an exponential decrease in yield ( Küppers et al, 2020 ). The form of the respective yield function might be dependent on the particle size distribution of the input material ( Figure 3 ) in dependence of the sorting algorithm.…”
Section: Resultsmentioning
confidence: 99%
“…The current research at the Chair of Waste Processing Technology and Waste Management of the Montanuniversität Leoben aims to quantify the impact of input composition and throughput rate (occupation density) on SBS. Küppers et al (2020) found the following systematic effects from prior SBS trials:…”
Section: Introductionmentioning
confidence: 99%
“…According to the above-mentioned definition, however, it is not so much the mass flow that is responsible for the influences on sorting quality shown above, but rather the occupancy density [163]. The density of occupancy describes the proportion of the sensory image that is actually occupied by material, compare Fig.…”
Section: B Mass Flow Occupancy Density and Proximitymentioning
confidence: 99%
“…This is partly because energy is required for the deflection process and partly because the deflection process itself potentially leads to sorting errors and should therefore be performed as rarely as possible [161] (see Sections III-D and V). Based on the Monte Carlo simulation [162] and experimental studies [163], an exponential decrease in the achievable mass flow is obtained with an increasing fraction of particles to be deflected while fixing the sorting quality.…”
Section: Materials Compositionmentioning
confidence: 99%
“…Within NEW-MINE, the influence of surface roughness and surface moisture of plastics on NIR sorting was investigated [48], and the findings were used outside NEW-MINE for material flow characterization in sensor-based sorting systems using an instrumented particle [49] and for a study of the influence of material alterations and machine impairment [50]. NEW-MINE learnings on the effects of throughput rate and input composition on sensor-based sorting [51] were subsequently used within the above mentioned ReWaste 4.0 project [47,52].…”
Section: Mechanical Processingmentioning
confidence: 99%